Learning Achievement: Understanding the Influence of Self-Confidence and Mathematical Disposition in Junior High School Students - Oktavia, Thessa; Yulia, Putri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study is to ascertain how class IX students at SMP N 4 Sungai Penuh self-confidence and mathematical disposition relate to one another. The 113 pupils in class IX of SMP Negeri 4 Sungai Penuh comprised the study's population. This study will use a probability sampling technique, specifically simple random sampling with the use of the Solvin formula, to select 30 students to serve as the sample. Correlational research is the type of study that this study is. The F test significance test, the Pearson product moment correlation calculation, and a comparison with the F table are the steps in the data analysis procedure utilized in this study. The study's findings suggest that self-confidence and mathematical temperament have a positive but negligible impact on the mathematics learning achievement of SMP N 4 Sungai Penuh class IX pupils. The study's findings demonstrated that, at a significance level of 0.022 < 0.05, the self-confidence variable had a positive and substantial impact on learning achievement. The mathematical disposition variable likewise significantly and favorably affects student learning achievement. Student learning achievement was positively and significantly impacted by the variables of self-confidence and mathematical disposition, with a coefficient of determination of 0,428.